Self-efficacy, parental involvement and school adjustment of high achieving secondary school students in Oyo State, Nigeria (2022)
This study investigated self-efficacy and parental involvement as predictors of school adjustment of high ability secondary school students in Oyo State, Nigeria. A descriptive survey design of correlational type was adopted. The simple random sampling technique was used to selective local government areas from each of the three senatorial districts in Oyo State. The simple random sampling technique was also used to select two secondary schools from each local government, while the purposive sampling technique was adopted to select 450 high achieving students in SSI (180 males and 270females), based on their scores in Slossan Intelligence test, and Achievement tests in English Language and Mathematics. Instruments used were Slossan Intelligence Test (r= 0.86); Mathematics Achievement (r=0.72) and English Language Achievement tests (r=0.75) Self-efficacy (r=0.72); and Parental involvement (r=0.81) while Pearson Products Moment Correlation was used to test, the hypotheses generated at 0.05 level of significance. Findings showed that self-efficacy (r=0. 98; P<0. 05), and parental involvement (r= 0. 97; P<0. 05) influenced school adjustment of high achieving secondary school students in Oyo State, Nigeria. Therefore, relevant government bodies and schools should adopt methods and different policies that can positively trigger positive aspects of these variables for exploitation in influencing school adjustment of high achieving students.